Police Officers' Perceptions of Body-Worn Video Cameras in Beijing. (September 2021) - Jiang, Feng; Xie, Chuanyu; Ellis, Tom
The Chinese police started using body-worn video cameras (BWVCs) from 2010 in some cities and provinces. On July 1, 2016, shortly after the death of Lei Yang during arrest by police, the Ministry of Public Security ( Gong'anbu ) introduced BWVCs as mandatory for all the Chinese frontline police officers through issuing Regulations on Audio and Video Recording of Onsite Law Enforcement for Public Security Units (RAVR). However, despite the nationwide use of BWVCs, the research literature on BWVCs in China remains sparse. Studies from the United States and the United Kingdom provide evidence of the importance of officers' buy-in to the new technology. It is, therefore, essential to know Chinese officers' views and evaluations of using BWVCs. Using an anonymized online questionnaire, adapted from published international prior studies, this article reports and evaluates the views of 255 Beijing officers of the Beijing Police Department. Our analysis suggests that, overall, there was a high level of support and a high level of self-reported use for BWVCs among respondents not only because they are required to use them but also because they wanted to. Officers perceived more benefits than disadvantages of using BWVCs and most thought BWVCs would help them in their daily work without reducing their enthusiasm for law enforcement. Some differences were found between officers from different working units and between male and female officers. There were also weak negative correlations between length of service as a police officer and supportive attitudes toward BWVCs. Most criticisms were about technical issues such as higher expectations on the battery life and BWVC reliability.